Peningkatan Kemampuan IT Guru PAUD Sekolah Penggerak Angkatan 2 Kabupaten Polewali Mandar - Nurhidayah, Nurhidayah; Arifin, Sartika; Aprisal, Aprisal (Pendidikan Matematika, FKIP Universitas Mataram, 2024)
A professional teacher must be able to innovate or develop creativity in learning through the use of technology. The aim of this community service activity is to improve IT skills for PAUD teacher at the Batch 2 driving school in Polewali Mandar district, West Sulawesi. Participants in this community service activity were PAUD teachers from 3 PGRI Kindergarten schools in Polman Regency, namely PGRI Polewali Kindergarten, PGRI Katumbangan Kindergarten, PGRI Al Kautsar Parappe Kindergarten. The method are divided into three stages, namely the preparation stage, implementation stage and evaluation stage. The main material for community service activities is training in operating Microsoft Word dan MS Excel Overall, this community service activity went well and smoothly. This was shown by the enthusiasm of the participants in following the activity until the end, the many questions asked by the participants at the end of the activity and even bringing their own laptops from home and the participants were able to operate MS. Office Word and Excel work well without feeling stiff.